2000
DOI: 10.1002/1096-8628(20001009)96:5<604::aid-ajmg5>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Detection of single nucleotide polymorphisms of the human mu opioid receptor gene by hybridization or single nucleotide extension on custom oligonucleotide gelpad microchips: Potential in studies of addiction

Abstract: The human mu opioid receptor (MOR) plays a central role in mediating the effects of opioids, both endogenous and exogenous. Epidemiological studies have shown that addiction in general, and especially opiate addiction, has a heritable component. Clinical and laboratory studies suggest that the MOR gene may contribute to the heritable component of vulnerability to develop opiate addiction. Naturally occurring single nucleotide polymorphisms (SNPs) have been identified in the MOR gene by conventional methods. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(19 citation statements)
references
References 86 publications
(168 reference statements)
1
17
0
1
Order By: Relevance
“…Finally Galanter et al [85] reported that patients more oriented toward a spiritual than a formerly religious affiliation toward other 12-step members (a spiritual awakening) associated with lower rates of substance seeking behavior. Evidence continues to emerge regarding our understanding of brain function especially the reward circuitry and all addictive behaviors and clinicians are encouraged to review some of the select molecular neurogenetic literature [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105].…”
Section: Beyound Vaillantsupporting
confidence: 90%
“…Finally Galanter et al [85] reported that patients more oriented toward a spiritual than a formerly religious affiliation toward other 12-step members (a spiritual awakening) associated with lower rates of substance seeking behavior. Evidence continues to emerge regarding our understanding of brain function especially the reward circuitry and all addictive behaviors and clinicians are encouraged to review some of the select molecular neurogenetic literature [86][87][88][89][90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105].…”
Section: Beyound Vaillantsupporting
confidence: 90%
“…It will also be of interest in future studies to determine whether any differences in response to oral naltrexone, such as those alluded to in this report with FHϩ persons, might be related to the presence of a heterozygous or homozygous state with respect to a very common allelic variant of the -opioid receptor gene A118G. This variant has been found by our group, in collaboration with the group of Dr. Lei Yu, to have both significantly greater binding and functional responses to the longest endogenous opioid, ␤-endorphin, than does the prototype or usual gene product (Bond et al 1998;Kreek 2000;LaForge et al 2000).…”
Section: Discussionmentioning
confidence: 72%
“…The design of oligonucleotide probes appears to be mandatory for resolving punctual sequence differences compared to PCR products that have been shown to exhibit poor performance for single-nucleotide polymorphism or punctual mutation analysis (19,27,29,38). Moreover, oligonucleotide probes are more flexible and can be tailored to meet critical criteria such as sequence specificity and physicochemical properties.…”
mentioning
confidence: 99%